Determinan Purchase Intention: Perspektif Pelanggan Minimarket - Hendika Rizkianti; Kurniawati Kurniawati (Journal of Management and Business Review, 2021)
The purpose of this research is to analyze the effect of brand awareness, perceived quality, brand association, and brand loyalty which affect the purchase intention of consumers at Alfamart minimarkets, Indomaret, Lawson in Jakarta. Distributing questionnaires to 200 respondents. In this study, sampling using non-probability sampling, in this study using purposive sampling. The data analysis method uses structural equation modeling (SEM) and AMOS22 software. The results show that the variable brand awareness, perceived quality, has a positive effect on purchase intention is not supported. Then brand association, brand loyalty also has a significant positive effect on the purchase intention of Alfamart, Indomaret, Lawson minimarkets in Jakarta. As for suggestions for the management of Alfamart minimarkets, Indomaret, Lawson in Jakarta in increasing brand awareness, perceived quality, companies that can influence consumer purchase intention at Alfamart minimarkets, Indomaret, Lawson in Jakarta.